التسويق الرقمي في المؤسسات الناشئة بين الواقع و التحديات - دراسة حالة مؤسسة " بريستو "(presto ) - - دومير عمار عبد القيوم; الاسود محمد (جامعة الوادي University of Eloued, 2024)
This study aimed to clarify the reality of digital marketing in start-upsand shed light on the challenges that the latter face in applying digital marketing. This is by linking the dimensions of digital marketing and the challenges of the start-ups. The questionnaire tool was used to collect information and the statistical program SPSS to extract the results of the questionnaire. Which was distributed to the management level of the start-up “Presto” in the state of Tebess.The study also found that the start-up، Presto، focused on two dimensions of digital marketing (learning and communication) and that it did not show much interest in the rest of the dimensions (attraction، participation،and retention).
Digital marketing in start-ups between reality and challenges- Presto case study
Keywords: تسويق رقمي; مؤسسات ناشئة; واقع; تحديات; بريستو